Interdiffusion and atomic mobility of the Mg–Sn–Zn system. (March 2023) - Yang, Li; Yuan, Yuan; Li, Qin; Wu, Jiajia; Chen, Tao; Wang, Jun; Zuo, Xiaojing; Tang, Aitao; Zhang, Lijun; Moelans, Nele; Pan, Fusheng
Abstract: Tin (Sn) and Zinc (Zn) are common alloying elements in magnesium (Mg) alloys. The thermodynamic and kinetic information of Mg–Sn–Zn system is necessary for understanding the solution and precipitation behaviour in Mg alloys. In the current work, series Mg–Sn–Zn/hcp-Mg, Mg–Zn/Mg–Sn and Mg-X (X = Sn or Zn)/hcp-Mg diffusion couples were assembled for the determination of the interdiffusion coefficients of the Mg-X (X = Sn or Zn) binary systems and Mg–Sn–Zn ternary system. The kinetic description of the hcp-Mg phase in Mg–Sn–Zn system was constructed. The features of the interdiffusion coefficients of different elements were discussed. Graphical abstract: Image 1